EFFECTS OF THE OPERATION OF CHAO PHRAYA DAM UPON THE UPSTREAM FLOOD HYDRAULICS - S. Visutimeteegorn; K. Likitdecharote; S. Vongvisessomjai (Lowland Technology International, 2006)
During flood periods, the operation of Chao Phraya Dam to control downstream water discharge causes flood inundation in upstream area, especially the water diversion in the irrigation areas. The purposes of this research are to study the effects of the operation of Chao Phraya Dam upon the upstream flood hydraulics and to study the harmony of the operation of Chao Phraya Dam, the regulators and the upstream reservoirs to model the flood situation with a hydrodynamic model and simulation techniques in flood inundation areas and for gate operation. The results shows that Manning’s n in the Chao Phraya River and its tributaries are 0.030 - 0.035 in the main channels and 0.050 – 0.070 in the flood plain areas. The backwater due to the operation of Chao Praya dam affects as far as 110 kilometers upstream. New methods of water diversion can mitigate the flood inundation and have no effect to the floating rice’s fields. The construction of the reservoirs in the Upper Sakaekang River Basin and the Upper Yom River Basin will mitigate the flood not only in their own basins but also in the Lower Chao Phraya River Basin. The operation of Chao Phraya Dam, the regulators and the upper reservoirs consistently will mitigate the flood inundation efficiently.